2022
DOI: 10.48550/arxiv.2205.07113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fidelity overhead for non-local measurements in variational quantum algorithms

Abstract: Measuring quantum observables by grouping terms that can be rotated to sums of only products of Pauli ẑ operators (Ising form) is proven to be efficient in near term quantum computing algorithms. This approach requires extra unitary transformations to rotate the state of interest so that the measurement of a fragment's Ising form would be equivalent to measurement of the fragment for the unrotated state. These extra rotations allow one to perform a fewer number of measurements by grouping more terms into the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The QWC scheme thus has a prima facie advantage in terms of circuit depth. For electronic Hamiltonians it has however been shown that this advantage is outweighed by other factors making the FC scheme preferable 18,19 in that case.…”
Section: Iib Measurement Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The QWC scheme thus has a prima facie advantage in terms of circuit depth. For electronic Hamiltonians it has however been shown that this advantage is outweighed by other factors making the FC scheme preferable 18,19 in that case.…”
Section: Iib Measurement Schemesmentioning
confidence: 99%
“…However, it has been shown empirically that the estimation of the electronic ground state of small molecules to chemical accuracy requires infeasible runtimes due to sampling overhead, which is called the measurement problem. 14,15 Different measurement schemes have been employed to reduce the sampling overhead, including the grouping of Pauli products into mutually commuting sets, [16][17][18][19][20][21][22][23][24][25] classical shadow tomography, [26][27][28][29] low-rank factorizations of the electronic Hamiltonian 30 and algebraic approaches. 31 Current studies have however only investigated electronic Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown 18 that M (ǫ) in the QWC techniques are typically higher than M (ǫ) in the FC techniques. Moreover, a recent study 22 compared M (ǫ) in FC and QWC techniques while accounting for the non-unit fidelities of the quantum gates implementing Ûα . This study demonstrated that even after considering fidelities of one-and two-qubit gates, the FC fragmentation methods usually have lower M (ǫ).…”
Section: Introductionmentioning
confidence: 99%